EVALUATION OF PROFESSIONAL DEVELOPMENT IN LITHUANIAN EDUCATION: PROBLEMS AND PROSPECTS - Targamadzė, Vilija; Vėbra, Aras Viligaila (Acta Paedagogica Vilnensia, 2008)
This article examines professional development evaluation as a concept and as a process taking place in Lithuania, weighing the theoretical ideal against its practical application. The article describes research done on various levels with key players in professional development evaluation from Ministry officials to teachers, and concludes that achieving our goals is possible and within our grasp. Means of doing so are included.